THE STUDY OF SLANG UTTERANCES IN BRICK MOVIE - Daynikita Merisabel; M. Bahri Arifin; Nita Maya Valiantien (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2020)
This study discussed about slang utterances found in the movie entitled Brick directed by Rian Johnson. It is interesting to conduct slang research on Brick movie since it is a unique neo-noir movie which portrays teenager’s life that speak in an invented slang in the ‘20s, ’30s, and ‘40s. By using descriptive qualitative method, the purpose of the study is to identify the types of slang appeared in the conversation and to observe the context behind the slang used in Brick movie. The slang data is analyzed based on the types of American Slang theory by Chapman (1988) and by Partridge (1933). To support the analysis of context, the writers used the Ethnography of Speaking by Hymes (1974). Regarding to the research findings, the writers identified that there are three types of slang used by the seven characters in Brick movie script, namely: student slang, primary slang and secondary slang. The most frequently type of slang is secondary slang with total of 12 data. Furthermore, the meaning of each slang utterances is not only based on dictionaries but also based on the context of situation, such as setting, participants, ends, act, key, instrumentalities, norms, and genre. In conclusion, this study showed that there are many aspects of slang which can be analyzed more deeply into several other branches of linguistics, such as sociolinguistic, pragmatic and semantic.